Disruption of LTBP4 Inhibition-Induced TGFβ1 Activation Promoted Cell Proliferation and Metastasis in Skin Melanoma by Inhibiting the Activation of the Hippo-YAP1 Signaling Pathway - Wang, Lina; Tang, Dongrun; Wu, Tong; Sun, Fengyuan (Frontiers in Cell and Developmental Biology, 2022)
Melanoma is a malignant tumor derived from melanocytes, which is the most fatal skin cancer. The present study aimed to explore and elucidate the candidate genes in melanoma and its underlying molecular mechanism. A total of 1,156 differentially expressed genes were obtained from the GSE46517 dataset of Gene Expression Omnibus database using the package “limma” in R. Based on two algorithms (LASSO and SVM-RFE), we obtained three candidate DEGs (LTBP4, CDHR1, and MARCKSL1). Among them, LTBP4 was identified as a diagnostic marker of melanoma (AUC = 0.985). Down-regulation of LTBP4 expression was identified in melanoma tissues and cells, which predicted poor prognosis of patients with melanoma. Cox analysis results discovered that LTBP4 with low expression was an independent prognostic factor for overall survival in patients with melanoma. LTBP4 inhibition reduced cell apoptosis and promoted cell proliferation and metastasis. These changes were correlated with the expression levels of caspase-3, Ki67 and E-cadherin. Further, as indicated by tumor formation study of nude mice, LTBP4 silencing improved the tumorigenic ability of melanoma cells. Knockdown of LTBP4 increased the percentage of active TGFβ1 secreted by melanoma cells. CTGF, Gyr61, and Birc5 expression levels were reduced, YAP1 phosphorylation was inhibited, and YAP1 was translocated from the cytoplasm to the nucleus in melanoma cells treated with TGF-β1. These effects were reversed by LTBP4 overexpression. As evidenced by immunofluorescent staining, Western blotting and luciferase reporter assay, LTBP4 overexpression activated the Hippo signaling pathway, which was characterized by the increased nuclear-cytoplasmic translocation of YAP1 and the enhanced phosphorylation of YAP1, MST1, and MOB1. In addition, the effects of LTBP4 overexpression on inhibiting CTGF, Cyr61 and Birc5 expression, promoting the apoptosis, and inhibiting the metastasis and proliferation of melanoma cells were reversed by the overexpression of YAP1 or MST1. In conclusion, the LTBP4-TGFβ1-Hippo-YAP1 axis is a critical pathway for the progression of skin melanoma.